Instagram and buying decision processes of restaurant consumers - Monika Pretty Aprilia (Asian Journal of Media and Communication, 2018)
Social media has changed the way people consume. One of the changes is how people eating outside at restaurant. People only need mobile phone to gather information when they feel hungry and look for a place to have dine. Consumers choose restaurants based on the information they get from social media. Consumers can decide which restaurant they would like to go just after checking its reviews and photos on Instagram. This research aims to find the information that consumers use in the buying decision processes. The data was collected through in-depth interviews with restaurant consumers who live in major cities in Indonesia. This study finds that price, location, and Instagram reviews have been considerations in the buying decision processes.